Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood

Le pouvoir calorifique supérieur d'espèces forestières méditerranéennes - DOAT, Jacqueline; VALETTE Ch., J; ASKRI, D; CAUMARTIN, L; BETTACHINI, M; MORO, M (Ann. For. Sci., 1981)
Le pouvoir calorifique supérieur (P.C.S.) est le maximum d’énergie que peut dégager une combustion. Il conduit au bilan énergétique d’un incendie de forêt. Rapporté au poids de matière sèche ou au poids de la seule matière organique, le P.C.S. permet de hiérarchiser les végétaux selon leur caractère énergétique. Bien que les P.C.S. croissent avec la lignification des tissus, ils conduisent au classement par ordre décrois5ant : - feuilles de bruyère arborescente, - feuilles de pin d’Alep, - feuilles d’arbousier et pousses terminales d’ajonc épineux, - feuilles de chêne vert et de chêne kermès. Les P.C.S. de ces espèces méditerranéennes sont supérieurs ou au moins égaux à ceux d’espèces de régions plus tempérées.
Keywords: combustion (voyant); espèces mediterranéenes; pouvoir calorifique supérieur